Phosphodiesterase type 3A (PDE3A), but not type 3B (PDE3B), contributes to the adverse cardiac remodeling induced by pressure overload. (July 2019) - Polidovitch, Nazari; Yang, Sibao; Sun, Huan; Lakin, Robert; Ahmad, Faiyaz; Gao, Xiaodong; Turnbull, Patrick C.; Chiarello, Carmelina; Perry, Christopher G.R.; Manganiello, Vincent; Yang, Ping; Backx, Peter H.
Abstract: Phosphodiesterase type 3 (PDE3) inhibitors block the cAMP hydrolyzing activity of both PDE3 isoforms, PDE3A and PDE3B, which have distinct roles in the heart. Although PDE3 inhibitors improve cardiac function in heart disease patients, they also increase mortality. Nevertheless, PDE3 inhibitors can provide benefit to non-ischemic heart disease patients and are used extensively to treat heart failure in dogs. Since the isoform-dependence of the complex cardiac actions of PDE3 inhibition in diseased hearts remains unknown, we assessed the effects of PDE3 inhibitors as well as gene ablation of PDE3A or PDEB in mice following the induction of non-ischemic heart disease by pressure-overload with transverse-aortic constriction (TAC). As expected, after 6 weeks of TAC, mice exhibited left ventricular contractile dysfunction, dilation, hypertrophy and interstitial fibrosis, in association with increased macrophage numbers, activation of p38 MAPK and elevated PDE3 activity. Chronic PDE3 inhibition with milrinone (MIL), at doses that did not affect either cardiac contractility or arterial blood pressure, profoundly attenuated the adverse ventricular remodeling, reduced macrophage number and diminished p38-MAPK activation induced by TAC. Surprisingly, whole-body ablation of PDE3A, but not PDE3B, provided similar protection against TAC-induced adverse ventricular remodeling, and the addition of MIL to mice lacking PDE3A provided no further protection. Our results support the conclusion that PDE3A plays an important role in adverse cardiac remodeling induced by chronic pressure overload in mice, although the underlying biochemical mechanisms remain to be fully elucidated. The implications of this conclusion on the clinical use of PDE3 inhibitors are discussed. Highlights: PDE3 inhibition protects against ventricular remodeling due to pressure-overload. This protection is associated with reduced p38 MAPK, calcineurin/NFAT activation. PDE3A, not PDE3B, ablation protects against adverse effects of pressure-overload. Cardiac PDE3 activity, PDE3A expression are increased with pressure overload.